Quantifying the enzootic leukosis virus threat: how prevalent is the natural infection in Crioulo Lageano cattle in southern Brazil? - G. V. Fonteque; M. S. Casa; G. S. N. Ribeiro; Z. Silva; C. I. G. Vogel; J. H. Fonteque; U. M. Costa; M. E. Saito; G. Giovambattista; S-N. Takeshima; L. C. Miletti (Brazilian Journal of Biology)
Abstract Enzootic Bovine Leukosis (EBL), is infectious disease affecting especially older animals, although animals of all ages can be infected with the Bovine Leukemia Virus (BLV). Crioula Lageana is a locally adapted, rustic and long-lived bovine breed, important as a genetic resource. However, little is known about its health status, making it difficult to preserve the breed. In this sense, this study aims to assess the prevalence of EBL/BLV in different animal categories of Crioula Lageana cattle. Then, blood samples were collected from 308 animals from different categories: bulls, cows, heifers and male and female calves, whereby these animals were derived from six farms located in nuclei of in situ conservation for the Crioula Lageana breed in Planalto Serrano de Santa Catarina, Brazil and the blood samples were analyzed with hemogram, ELISA and PCR tests. There was a prevalence of 6.82% (21/308) for the ELISA test and 36.69% (113/308) for the PCR technique. There was no association between categories and natural infection or BLV positivity in PCR by the Chi-square test (P<0.05). Leukocytosis with lymphocytosis was observed in 11% (18/113) of PCR-positive animals. None of the evaluated animals presented bovine lymphosarcoma. We conclude that the BLV is present in all animal categories of the Crioula Lageana cattle, requiring the establishment of prevention and control measures to avoid the spread of the disease within herds.